Interaksi Sosial Masyarakat Kelurahan Manembo Nembo Tengah Kecamatan Matuari Kota Bitung - Putra, Taufan Eka; Kaunang, Markus; Mingkid, Elfie (JURNAL ILMIAH SOCIETY, 2015)
The interaction between man and man became a necessity to make ends meet. This study was conducted to determine and analyze the social interaction that occurs in the community in the Village of Central District of Matuari Manembo Nembo Bitung as a scientific development, especially the development of power cracked management science in the study of resource management. This study used a qualitative method with the main data comes from interviews with informants is a representation of the village government, environmental coconut, minahasa ethnic communities, ethnic communities Sangihe, Javanese ethnic communities and ethnic communities Gorontalo and other supporting data obtained through direct observation and the use of related documents . The conclusion of this study is the social interaction that occurs in communities in Sub-nembo Manembo Middle District of Matuari Bitung relating to cooperation seen in everyday life, birth, marriage and kinship systems. Keywords: Social Interaction, Community, Kinship.